Dissimilarity of Female and Male Early Childhood Cognitive and Social Emotional (Martabat: Jurnal Perempuan dan Anak, 2020)
The present research aims to identify cognitive dissimilarity and social-emotional for both male and female toddlers. The method of this study is library research. The data were analyzed according to some literature reviews and scientific research reports. To analyze the data, the researcher uses content analysis. The result of this study shows that cognitive dissimilarity between either male and female children is according to their competence in math, visual-spatial, and verbal competence. Then, the dissimilarity of social-emotional between both male and female children are based on their empathy, sense of helping others, caring to the environment, respect to the teachers, have a strong will to learn, and prosocial behaviors. The factors that influence cognitive dissimilarity and social-emotional of both female and male children are biological factors, social factors, parenting, friends, teacher factor and school environment, and also the role of media. The implication is, either parents or teachers need to understand and accept that dissimilarity and try to find out some strategies to stimulate the children’s cognitive and social-emotional development for both female and male toddlers.